Strategi Pemasaran pada Beryl Coffee Tawangmangu Malang - Setiawan, Terrance Jovanus; Sugeha, Anisa Zuhria; Sari, Nadia Roosmalita (Jurnal Pariwisata Tourista, 2023)
The business world is growing in various sectors, this is very influential on competition - competition in the business world which is increasingly widespread. In this case, it can make the company know what kind of marketing strategy it is and how to implement it. At this time consumer interest is increasing towards Coffee Shop, even in almost all big cities. Not only students and students, but also adults who are interested in coffee shops. Therefore, researchers conducted research on marketing strategies at Beryl Coffee Malang, at Jalan Tawangmangu No. 21. This research uses descriptive qualitative method with SWOT analysis. With the aim of knowing a good and appropriate marketing strategy for Beryl Coffee, it also draws conclusions from a SWOT analysis. Researchers use IFAS to conduct environmental research, using IFAS which contains the strengths and weaknesses of the company. Furthermore, using EFAS which contains an analysis of opportunities and threats for the company. From the results of the study, it can be concluded that in the SWOT diagram, Beryl Coffee's position is in quadrant 1, namely that this position has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that can be used in this condition is to support an aggressive growth policy (growth oriented strategy).